"在" 介词短语中方位词的隐现 —— 基于新加坡华语师生的调查研究 = The use of localisers in zai prepositional phrases among Singapore Chinese teachers and students - 蔡勇乐 Chua, Yong Le (Nanyang Technological University, 2024)
相较于英语介词短语，现代汉语的介词短语常使用介词“在”，且在名词短语(NP) 后使用方位词 (L) ，即“在+NP+L”。其中，“在+NP+L”介词短语中方位词的隐现是新加坡学生常见的偏误之一。不过现有文献基本聚焦于汉语学习者的偏误现象，却忽略了进行教学任务的教师本身是否具有与语法规范相同的语感。因此，为了填补这一研究空白，本文同时针对新加坡中学生和教师进行调查，发现师生总体倾向于在介词短语中使用方位词，其趋势与新加坡教育部指定教材所反映的一致。然而，本文发现师生之间对于“在+NP+L”介词短语中是否该带方位词的认识存在分歧。第一，师生之间对于介词短语中名词性短语性质的认识不一致，导致他们在该名词性短语是否必带方位词的问题上没有共识。这个分歧不仅存在于两组参与者之间，在同一组参与者中亦然。第二，对于性质相近的名词性短语，师生对于它们方位词隐现的处理方式亦有差别，反映了他们个人语感的不一致。本文通过观察师生的语用情况，从新加坡华文教育当中探讨新加坡华语语法相较于普通话或其他现代标准汉语的特征，更客观地考虑何为新加坡华文教学中的“语法规范”。 zai is a commonly used preposition in the Chinese language. As compared to English prepositional phrases, the noun phrase following zai often carries a localiser, which forms the “zai+NP (noun phrase) +L (localiser)” prepositional phrase structure. The optional uses of localisers in zai prepositional phrase is a common cause of grammatical error among Singapore secondary students due to the differences between English and Chinese languages. Existing literatures acknowledge and explain the error patterns of language learners as opposed to “proper” grammatical norms, yet do not consider if teachers share the same understanding and intuition aligned with the grammatical norms. This study aims to address this research gap, given the importance of their role when imparting linguistics knowledge to students, by conducting research on Singapore teachers and secondary school students. It has been found that the teachers and students have a preferential usage of localisers in “zai+NP+L” prepositional phrase, a pattern consistent with how “zai+NP+L” prepositional phrases are reflected in the prescribed textbooks by Singapore Ministry of Education. However, there are discrepancies as to when to include a localiser in the “zai+NP+L” prepositional phrase. Firstly, there are differing views on the nature of the different noun phrases within the prepositional phrase, leading to a lack of consensus on whether localisers are optional. Such differences occur not only between these two groups of participants, but also within the group itself. Secondly, when noun phrases are of similar nature, teachers and students exhibit differences when using localisers in the prepositional phrase, reflecting the inconsistencies in their individual linguistics intuition. This paper explores, in the context of Singapore Chinese language education, the characteristics of Singaporean Mandarin grammar as compared to Putonghua or other varieties of Mandarin Chinese, to consider more objectively what constitutes as “grammatical norms” in Singapore Chinese classrooms.